(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The cause of unexplained subfertility has remained a persistent clinical dilemma and intrauterine insemination (IUI) has been employed as an initial treatment method. Nonetheless, the results of treatment depend on the population of patients and the clinical conditions. Objective: To evaluate the clinical outcomes of IUI, and determinants of success in couples with unexplained subfertility receiving treatment at a tertiary care hospital. Methods: The retrospective observational study was carried out in the Department of Gynecology and obstetrics, Lady Willingdon Hospital, Lahore with the sample population of 120 couples undergoing 240 IUI cycles. Demographic information, cycle variations, semen variables, and pregnancy results were studied. The factors that were found to be independent predictors of clinical pregnancy were identified by means of multivariable logistic regression. Results: The live birth rate was 8.3 and the clinical pregnancy rate per cycle was 10.8. Increased age of women at the time of birth, reduced infertility years, endometrial thickness with 8-mm cut-offs, and post-wash total motile sperm count with 10-million cut-offs were found to be associated with the increased rate of pregnancy. The rate of multiple and ectopic pregnancy was low. Conclusion: Intrauterine insemination can be used as a viable and availed therapy to unexplainable subfertility in tertiary care. With the correct selection of patients and personalized control of the cycles, it is possible to optimize the outcomes.